Agglomeration or market access? The defining factors of firms' location choice - Dennis Gaus; Georg Hirte (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
As research indicates a gap between complex scientific measures of accessibility and simpler proxies used by firms, this paper analyses the impact of several market access indicators on the location decision of firms. It compares the role of inter- and intra-industry agglomeration as proxies of access with a newly developed gravity-based indicator incorporating transport distances and industry relations. The estimation results of a nested mixed multinomial logit model, based on a sample of 110,083 German firms, provide evidence that agglomeration effects play an essential role in firms' location choice, whereas the complex market access measure does not have a significant impact. This outcome holds true for large as well as small and medium sized enterprises and is confirmed in several robustness checks. Thus, the paper provides guidance to further research on companies' location decisions, highlighting that access indicators should be chosen specifically for the scientific context, as well as to firms to make more efficient location choices from the perspective of market access.
Keywords: L14; O18; R12; R32; 330; Transportation; Accessibility; Location Choice; Agglomeration; Market Access